Crossing boundaries, building bridges : comparing the history of women engineers, 1870s-1990s - Canel, Annie; Oldenziel, Ruth, 1958-; Zachmann, Karin (Studies in the history of science, technology, and medicine, 2000)
These papers provide an investigation of the contribution made by women to the traditionally male-dominated industry of engineering. Women engineers are looked at in an historical context, and from a cross-cultural and socio-economic perspective.